FLYPAPER EFFECT DAN BELANJA DAERAH DI PROPINSI JAWA BARAT - Rifki Hasan Al Khoiri (Signifikan: Jurnal Ilmu Ekonomi, 2015)
The purpose of this study was to determine whether PAD, DAU and DAK influence to government local expenditure according to Simultaneous and Partial both in areas that are in West Java and also to determine whether there has been a flypaper effect in areas that are in the West Java on 2008 – 2012.  Object of this study focuses on the entire region in West Java Province, totaling 26 districts / cities.The method of analysis used in this study is a data panel with Pooled Least Square (PLS). The results of this study stated that partial PAD, DAU and DAK significantly influence to government local expenditure in the region of West Java province on 2008 – 2012, because Probability value of PAD is 0,000 < 0,05. DAU is 0,000 < 0,05, and DAK is 0,02 < 0,05. Simultaneously PAD, DAU and DAK also significantly affect to government local expenditure because probsbility value is 0,000 < 0,05. In this study, results were obtained that did not happen flypaper effect where revenue source is derived from the PAD was greater affect the amount of spending in the next yearDOI: 10.15408/sjie.v4i2.2306